Does public information about school quality lead to flight from low-achieving schools? - Jane Friesen; Mohsen Javdani; Simon Woodcock (Institute for the Study of Labor (IZA), 2009)
We estimate the effect of publicly disseminated information about school-level achievement on students' mobility between elementary schools. We find that students are more likely to leave their school when poor school-level performance is revealed. In general, parents respond to information soon after it becomes available. Once the information is absorbed, they do not respond to subsequent releases, even when it is reframed and given widespread media attention. Parents in low-income neighborhoods and those who speak a non-English language at home respond most strongly. However, non-English speaking parents only respond when information is widely disseminated and discussed in the media.
Keywords: I21; 330; Information; school choice; Schulauswahl; Informationsverhalten; Allgemeinbildende Schule; Dienstleistungsqualität; Öffentliche Meinung; Kanada